Effect of self-etching dual-curing universal adhesive system application on bond strength of dentin resinous liners dentin - Zanatta, Rayssa Ferreira [UNESP] (2016)
Purpose: The aim of this study was to evaluate the influence of previous application of an adhesive system on bond strength of resinous liner materials to dentin. Methods: Ninety bovine incisors crowns had a 6 x 6 mm area of dentin exposed, with minimum of 2 mm thickness. They were embedded in acrylic resin, and the dentin was polished with P600 SiC sandpaper for 30 s to standardize the smear layer. The specimens were divided into 6 groups (n = 15) according to the application or not of a self-etching system (Futurabond U - Voco) and the type of resinous liner used: A+Ionoseal (adhesive and Ionoseal-Voco); Ionoseal (Ionoseal only); A+Vitrebond (adhesive and Vitrebond - 3M/ESPE); Vitrebond (Vitrebond only); A+Ionosit (adhesive and Ionosit - DMG) and Ionosit (Ionosit only). Adhesives were used following manufacturer's instructions, and the liner materials were applied inside a 2-mm-depth matrix and light-cured for 20 s. The bond strength was measured by microtensile test, using a universal testing machine with a cross-speed of 1 mm/min. Data were analyzed using one-way ANOVA and Tukey's test (p < 0.05). Results: The adhesive system application increased bond strength of all liners tested. Ionoseal presented the highest bond strength when the adhesive system was used and exhibited similar performance to Vitrebond without adhesive. Ionosit without adhesive showed the smallest bond strength compared with the other liners tested. Conclusion: The application of an adhesive system prior to the use of the resinous liners improved the bond strength to dentin and should be preconized.